Examination of Primary School Students' Exam Success in terms of Controllable Variables by Logistic Regression Analysis - YarÄ±m, Mehmet Ali; BedirhanoÄŸlu, IÅŸÄ±l (Mimbar Sekolah Dasar, 2021)
This descriptive research using the relational screening model aims at examining the controllable variables that affect students' exam success. In this research, the problems of whether the time spent by the students with their families, having a study desk or room at home, having a library at home and the time spent on digital screens affect student success. The research study group consists of third- and fourth-grade students from 20 primary schools in various provinces of Turkey, selected by a convenient sampling method in the years 2020-2021. Variables with the achievement evaluation exam were prepared by the field teachers for the student's exam scores and controlled by the expert teachers. The data obtained in the research were analyzed assisted by the SPSS program with descriptive and logistic regression analysis. The research results concluded that students who have a room or a desk at home, have a library at home, spend quality time at home with their family in the evenings, and feel happy at home can increase student success in primary schools.